2021
DOI: 10.1111/1348-0421.12923
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory axis (programmed death‐1/programmed death ligand‐1) on CD4+ T cells in lupus nephritis: association with vitamin D and chemokine C‐X‐C motif ligand 12

Abstract: Lupus nephritis (LN) is one of the most serious complications of systemic lupus erythematosus (SLE). Multiple immunomodulatory mechanisms contribute to the pathogenesis of LN. A deep understanding of the immunopathogenesis of LN is essential to identify optimal molecular targets, as most immunotherapeutic algorithms are still based on unselective drugs. The study aimed to elucidate the possible association of vitamin D deficiency with the programmed death‐1 (PD‐1)/programmed death ligand‐1 (PD‐L1) axis and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Most investigators support a destructive effect of PD1 expression in LN as the frequency of CD4+PD1+ and CD4+CXCR5−PD1+ peripheral T cells has been correlated with increased levels of INF-gamma and IL-17, as well as with disease activity [27,28]. Meanwhile, others have shown that the PD1/PDL1 ratio is reduced in active LN, with vitamin D playing central role in the inflammatory immune process [29]. Moreover, exhausted CD8+PD1+ T cells exert a reduced cytotoxic function and a reduced capacity of IL-2, IFN-γ, and TNF production [30].…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators support a destructive effect of PD1 expression in LN as the frequency of CD4+PD1+ and CD4+CXCR5−PD1+ peripheral T cells has been correlated with increased levels of INF-gamma and IL-17, as well as with disease activity [27,28]. Meanwhile, others have shown that the PD1/PDL1 ratio is reduced in active LN, with vitamin D playing central role in the inflammatory immune process [29]. Moreover, exhausted CD8+PD1+ T cells exert a reduced cytotoxic function and a reduced capacity of IL-2, IFN-γ, and TNF production [30].…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] As opposed to SLE patients without lupus nephritis (LN) and healthy controls, patients with LN exhibit higher levels of CD274. 30 When compared to healthy controls, SLE patients exhibit higher CD274 expression in peripheral blood neutrophils, which is correlated with disease activity and severity. 31 Dendritic cells (DCs) are important for the immune response and maintain the proper ratio of tolerance to immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have discussed CD274 in autoimmune disorders such as RA, SLE, and type I diabetes 27–29 . As opposed to SLE patients without lupus nephritis (LN) and healthy controls, patients with LN exhibit higher levels of CD274 30 . When compared to healthy controls, SLE patients exhibit higher CD274 expression in peripheral blood neutrophils, which is correlated with disease activity and severity 31 .…”
Section: Discussionmentioning
confidence: 99%